DAMPAK PENERAPAN GREEN ACCOUNTING DAN KINERJA LINGKUNGAN TERHADAP PROFITABILITAS DENGAN GOOD GOVERNANCE SEBAGAI VARIABEL MODERASI - Helmi Attariq Fadhlurrahman; Zulfikar Zulfikar (ITB AAS Indonesia Surakarta, 2024)
This research aims to determine the effect of Green Accounting, Environmental Performance with Good Corporate Governance as measured by the Board of Directors and Audit Committee on Profitability. The research method used is a quantitative method. The population used in this research is Manufacturing Sector Companies Listed on the Indonesian Stock Exchange in 2020-2022. The sampling technique used in this research is purposive sampling consisting of 135 Manufacturing Sector Companies Listed on the Indonesia Stock Exchange in 2020-2022. The results of this research indicate that Green accounting has no effect on profitability. that Environmental Performance Influences Profitability. Good corporate governance as measured by the number of board of directors does not strengthen the relationship between green accounting and profitability. Good corporate governance as measured by the number of audit committees does not strengthen the relationship between green accounting and profitability. Good corporate governance as measured by the number of board of directors does not strengthen the relationship between environmental performance and profitability. Good corporate governance as measured by the number of audit committees does not strengthen the relationship between environmental performance and profitability.